Immigration, obesity and labor market outcomes in the UK - Susan L. Averett; Laura M. Argys; Jennifer L. Kohn (IZA Journal of Migration, 2012)
We estimate the dual effects of immigration and obesity on labor market outcomes in the UK using the British Household Panel Survey. We find support for the healthy immigrant hypothesis and evidence that immigrants' weights increase with time in the UK. While overweight and obese men enjoy a wage premium, overweight and obese immigrant men face a wage penalty and are less likely to work in a white collar job. Overweight immigrant women are substantially more likely to suffer work limitations. While data limitations preclude efforts to address endogeneity, these associations suggest that immigrants have not been spared from the obesity epidemic.
Keywords: 330; immigrant; obesity; labor market outcomes; Migranten; Körpergewicht; Arbeitsmarktintegration; Arbeitsmarkt; Großbritannien